Psychometric validation and testing of the 10-item pediatric daily chest-related electronic patient reported outcome (ePRO) diary - Rob Arbuckle; Tim Shea; Kate Burrows; Chris Marshall; Andrew Trigg; Julia Stein; Helmut H. Albrecht (SpringerOpen, 2023)
Abstract Background and objective The chest-related electronic patient reported outcome (ePRO) diary was recently developed to assess chest-related symptoms experienced by pediatric and adolescent populations during upper respiratory tract infections (URTI). The objective of this research was the psychometric evaluation of the chest-related ePRO diary in pediatric, adolescent and adult participants. Methods This non-interventional, psychometric validation study involved participants (N = 195; n = 42 6-8 years; n = 47 9-11 years; n = 55 12-17 years, n = 51 18+ years) completing the chest-related ePRO diary twice daily for 10 days while experiencing an acute URTI. Preliminary item-level performance and dimensionality results, along with consideration of previous qualitative findings, were used to inform item reduction decisions, the structure of the measure and scoring algorithm development. Subsequent analyses on the finalized measure included assessments of reliability (internal consistency and test-retest reliability), construct validity (convergent validity and known groups validity) and ability to detect change. Comparisons of findings were made between the different age groups as part of the analyses to assess the psychometric properties of the chest-related ePRO diary and to characterize potential differences in the symptom experience of children, adolescents, and adults. Results The measure demonstrated strong quality of completion and showed relatively similar trajectories of symptom scores over time within different age subgroups and good item response distribution properties. Exploratory factor analysis supported a one-factor solution in the total population and within age subgroups, and test-retest reliability of the measure was strong (Intra-class correlation: 0.843-0.894 between Visit 1 and Day 1). The measure also demonstrated strong construct validity through high correlations with relevant items on the Child Cold Symptom Questionnaire (CCSQ), strong known groups validity (with statistically significant differences between severity groups) and was responsive to change over time with change groups defined based on change on global items. Conclusion The findings demonstrate that the chest-related ePRO diary provides a valid, reliable, responsive measure of chest congestion symptoms experienced with the common cold in pediatric and adolescent populations, and that only minor differences are present in the disease trajectory when comparing adults to younger participants, supporting the use of the measure in interventional studies.